Factors related to teenage pregnancy during the COVID‑19 pandemic: a case of selected villages in Mayuge District, Eastern Uganda - Batiibwe, Marjorie Sarah Kabuye; Nannyonga, Betty K.; Nalule, Rebecca M.; Mbabazi, Fulgensia K.; Kyomuhangi, Annet; Mbabazi, Doreen S.; Namusoke, Sylvia S.; Namugaya, Jalira; Taliba, Caroline; Nakakawa, Juliet N. (SN Social Sciences, 2023)
The COVID-19 pandemic and related school closures had considerable consequences on teenagers’ sexual activity, thus increasing teenage pregnancy. This study aimed to establish factors related to teenage pregnancy in selected villages in Mayuge District. Data were collected from 38 teenage mothers/pregnant teenagers through face-to-face in-depth interviews and analyzed using thematic analysis. Findings from this study indicate that factors related to teenage pregnancy were: individual, social, economic, and physical setting factors. Furthermore, the challenges the participants faced included a lack of maternal knowledge, postpartum depression, unsupportive partners, and a lack of social and survival skills for self-sustenance. The implication is that there is an urgent need to look for ways to reduce the magnitude of teenage pregnancy. Accordingly, we recommend that relevant authorities formulate community-based programs for the sensitization of teenagers, parents, and communities on sex and reproductive health, in addition to the incorporation of sexuality education in the school curriculum.